Undergraduate Nursing Students' Attitude and Perception Toward High-Fidelity Simulation-Based Education in a Middle Eastern Country - Savithri Raman RN, RM, MSN; Judie Arulappan RN, RM, MSN, PhD, DNSc, CHSE; Omar Al Zaabi RN, MSN, PhD; Iman Al Hashmi RN, MSN, PhD; Sophia Cyril Vincent RN, RM, MSN; Divya Raghavan RN, RM, MSN; Sathiyamurthi Panchatcharam (SAGE Publishing, 2024)
Introduction Rapid use of technologically driven simulation environment in teaching-learning has caused mixed feelings among students. High-fidelity simulation-based education is superior in cultivating the knowledge, skills, caring, learning interest, and collaboration among nursing students. However, the nursing students' attitudes and perceptions toward high-fidelity simulation-based education are unexplored. Objectives The present study aims to explore the attitude and perception of undergraduate nursing students toward high-fidelity simulation-based education. Methods Cross-sectional survey research design was adopted. We used self-administered Education Practices Questionnaire (student version) and Attitude Scale toward Simulation-Based Education to collect the data. A total of 109 nursing students were recruited. Results Nursing student's attitude shows (mean = 68.26); perception on educational practices of high-fidelity simulation-based education demonstrates ( M  = 39.33 ± 7.87) and the importance of high-fidelity simulation-based education shows ( M  = 37.73 ± 7.45). However, no significant difference observed between the male and female student's attitude ( t  = −0.286 [0.78]) and perception ( t [107] = 0.960 [0.34]). Similarly, no significant difference was observed among the different levels of students p  > .005 on perception and attitude toward high-fidelity simulation-based education. Conclusion The study proposed to have high-fidelity simulation-based education as an integral part of teaching in clinical training of students at all levels of nursing program.